(untitled) (Raparin Journal of Humanities (RJH), 2024)
This study analyzes, the characteristics of solar energy in the Kurdistan Region, solar energy is considered one of the most important elements of climate, Because the increase and decrease of this important species affect all other species, the reason for choosing this study is due to the importance of this topic that has not been properly worked on in the field of climate geography in Kurdistan. To reach an accurate result, the researcher took (10) weather stations in different areas of the study area such as (Amedi, Haji Omeran, Halsho, Mosul, Soran, Erbil, Kirkuk, Sulaimani, Halabja, and Kalar), In this study, the analytical method was used, the researcher reached several important conclusions that include the suitability of the study area to rely on this energy, Because, the annual value of solar energy reaching the roof of the Atmosphere at the level of the study area reaches (29.68) megajoules/m2/day. The average total solar energy reached the level in the study area reaches (15.85) megajoules/m2/day. To a large extent, the amount of total solar energy available varies from year to year It contains stability. On the other hand, the results of the classification of total solar energy in the study area, showed that in (52.12) days more than (15) megajoules / m2 / day.